1999
DOI: 10.1162/089892999563373
|View full text |Cite
|
Sign up to set email alerts
|

ERP Manifestations of Processing Printed Words at Different Psycholinguistic Levels: Time Course and Scalp Distribution

Abstract: The aim of the present study was to examine the time course and scalp distribution of electrophysiological manifestations of the visual word recognition mechanism. Event-related potentials (ERPs) elicited by visually presented lists of words were recorded while subjects were involved in a series of oddball tasks. The distinction between the designated target and nontarget stimuli was manipulated to induce a different level of processing in each session (visual, phonological/phonetic, phonological/lexical, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

108
617
21
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 655 publications
(750 citation statements)
references
References 82 publications
108
617
21
4
Order By: Relevance
“…Stroop-like paradigms have been used to study synesthesia in the lab (e.g., Odgaard et al, 1999;Bergfeld-Mills et al, 1999;Dixon et al, 2000). Others have used variants of visual search paradigms in synesthetes to address the perceptual reality of color-grapheme synesthesia (Palmeri et al, 2002;Ramachandran and Hubbard, 2001a).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stroop-like paradigms have been used to study synesthesia in the lab (e.g., Odgaard et al, 1999;Bergfeld-Mills et al, 1999;Dixon et al, 2000). Others have used variants of visual search paradigms in synesthetes to address the perceptual reality of color-grapheme synesthesia (Palmeri et al, 2002;Ramachandran and Hubbard, 2001a).…”
Section: Methodsmentioning
confidence: 99%
“…Synesthetes' typically report that synesthesia is experienced as soon as the inducer is seen. ERPs to orthographic and non-orthographic material diverge as soon as ~150ms post stimulus presentation (Bentin et al, 1999). Indeed preliminary ERP data from both AD and CP suggested that by 150-200ms the responses to congruently and incongruently colored letters differ (Sagiv, Knight, and Robertson, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple P1 generators have been identified, with the largest activity observed over dorsal stream sites, with extrastriate (V3, V3a and middle occipital gyrus) (Di Russo et al, 2001;Vanni et al, 2004) as well as striate contributions (Aine et al, 1995;Maier et al, 1987;Vanni et al, 2004). P1 is followed by N1, a negative deflection peaking at approximately 150 ms with multiple generators that may represent P-mediated activation of ventral stream structures such as lateral occipital complex (Bentin et al, 1999;Doniger et al, 2000Doniger et al, , 2001Doniger et al, , 2002). …”
Section: Introductionmentioning
confidence: 99%